Financing National Infrastructure: The Role of Sovereign Capital Mobilization Strategies - Nana Dwemoh Benneh (International Journal of Computational and Experimental Science and Engineering, 2022)
Financing national infrastructure remains a critical challenge for governments seeking to support sustainable economic growth and development. This study examines the role of sovereign capital mobilization strategies in enhancing infrastructure financing capacity and improving infrastructure development outcomes. Using a quantitative research design, the study integrates composite indices, panel regression analysis, and canonical correlation analysis to evaluate the relationship between sovereign capital mobilization mechanisms and infrastructure investment performance. The findings reveal that sovereign capital mobilization strategies, including development finance capacity, public-private partnership intensity, asset recycling strategies, and blended finance utilization, significantly contribute to improved infrastructure investment intensity and financing efficiency. The results further indicate strong multivariate relationships between sovereign capital mechanisms and infrastructure development indicators. Trend analysis also demonstrates a consistent increase in infrastructure investment aligned with improvements in sovereign capital mobilization strategies. The study highlights the importance of diversified financing approaches, institutional capacity, and governance frameworks in mobilizing sovereign capital for infrastructure development. Overall, the findings suggest that sovereign capital mobilization provides a sustainable pathway for addressing infrastructure financing gaps and strengthening long-term economic development.